Combining Endoscopic Submucosal Dissection and Adjuvant Chemoradiotherapy or Radiotherapy for Effective Management of Rectal Cancer with Deep Submucosal Invasion: A Case Series - Ji Hye Park; Jae Hyun Kim; Sung Hyun Ko; Seun Ja Park (The Korean Journal of Gastroenterology)
Rectal cancer is one of the most prevalent malignancies worldwide, and the introduction of an endoscopic submucosal dissection (ESD) has offered minimally invasive management for early colorectal cancers. On the other hand, a post-ESD pathological examination showed that the risk of lymph node metastasis increases with deep submucosal (SM) invasion, positive lymphovascular invasion, grade 2/3 tumor budding, and certain histological types. An intestinal resection with a lymph node dissection is recommended in these cases, and chemoradiotherapy (CRT) is also effective adjuvant therapy. This paper reports a case series of patients who underwent ESD for rectal cancer and received concurrent CRT because of pathologically confirmed deep SM invasion.